2016
DOI: 10.1016/j.ijcard.2016.05.065
|View full text |Cite
|
Sign up to set email alerts
|

Screening pulmonary arteriovenous malformations in a large cohort of Spanish patients with hemorrhagic hereditary telangiectasia

Abstract: No grade 1 patients had treatable PAVMs. There is a need for improvement in the selection of patients for CT in grade 2, where less than half have PAVMs on CT. The cardiac cycle may help to differentiate between patients with and without PAVMs. Gelofusine was not better than saline for PAVM screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Moreover, none of the grade 1 shunts subsequently needed embolization, whereas 25.3% of grade 2 shunts and 77.4% of grade 3 shunts required endovascular closure of PAVM. Other studies have reported similar observations, for example that increased shunt grade predicts presence of PAVM on chest CT [24][25][26], and that patients with grade 1 shunts do not receive intervention, whereas those with grade 2 and 3 shunts often do [27][28][29][30].…”
Section: Transthoracic Contrast Echocardiographysupporting
confidence: 53%
“…Moreover, none of the grade 1 shunts subsequently needed embolization, whereas 25.3% of grade 2 shunts and 77.4% of grade 3 shunts required endovascular closure of PAVM. Other studies have reported similar observations, for example that increased shunt grade predicts presence of PAVM on chest CT [24][25][26], and that patients with grade 1 shunts do not receive intervention, whereas those with grade 2 and 3 shunts often do [27][28][29][30].…”
Section: Transthoracic Contrast Echocardiographysupporting
confidence: 53%
“…These schemes have identified a threshold of contrast below which further imaging is not required, as a treatable PAVM is unlikely to be found. 15,[37][38][39] The shunting associated with PAVM differs from that seen with PFO or other intracardiac shunts in that the contrast appears late after initial injection 37 (requiring time to transit from the right ventricle to the lungs and back to the left heart), whereas intracardiac shunt has the potential to appear early after injection (a threshold of three cardiac cycles or less tends to be used to define "early" shunt). Intracardiac shunt is also typically increased by the Valsalva maneuver by reversing the intracardiac left-to-right pressure gradient, where no increase in shunt is seen for PAVM with Valsalva.…”
Section: Saline Contrast Echocardiographymentioning
confidence: 99%
“…However, these abnormal communications between pulmonary arteries and veins are commonly seen in patients with hereditary hemorrhagic telangiectasia (HHT) (also known as the Osler-Weber-Rendu syndrome) [2,3]. Aside from the congenital etiology, several conditions may lead to acquired forms of multiple PAVFs-including cirrhosis, chest trauma, metastatic carcinoma, schistosomiasis, and systemic amyloidosis [4,5].…”
Section: Introductionmentioning
confidence: 99%